The Development and Education Application of Editable University Digital Museum - Yang, Yu Hui; Zhang, Hao; Jiang, Bin You (International Journal of Online and Biomedical Engineering (iJOE), 2015)
Currently most of the university digital Museums are confronted with such issues like lacking immersive, loading content slow, failing to update their 3D digital resources, can’t extend their virtual exhibition space and change their styles. In order to solve these problems, an editable university digital museum system (EUDMS) was proposed in this paper. Firstly, we analyzed the major problems of the university digital museums at present. Next, we designed a novel architecture of editable university digital Museum and realized it. Finally, a typical editable university digital Museum system was applied in the humanities education.